IDENTIFIKASI BAKAT OLAHRAGA SISWA KELAS VII SMP NEGERI 1 ANDONG BOYOLALI TAHUN 2020 - Joko Supriyono; Slamet Santoso; Widha Srianto (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2021)
The purpose of this study was to determine the potential talents in the sports field of students at SMP Negeri 1 Andong Boyolali Regency in 2020. Knowing whether or not the student has a sports potential in the sports they are participating in. This type of research is descriptive quantitative, using test and measurement techniques. One-shot case study research design. The population in this study was 217 students, the sample of this study was 50 students who were taken by purposive sampling. The instrument used is the Sport Search method. Based on the results of the study, it can be concluded that the talents or hobbies of the students include soccer as many as 33 students or 66%. According to 7 students, 13 students did not match, and 13 students did not match. Volleyball sports as many as 15 students or 30%. According to 9 students, less suitable for 1 student, not suitable for 5 students. Basketball as many as 2 students or 4%. According to 0 students, less suitable for 0 students, not suitable for 2 students. The total number of students who are not suitable and not suitable is 34 students or 68%. Has the potential in the sport of fast walking 9 students or 18%, high jump 10 students or 20%, 10 students or 20% shot put, 5 students running or 10%. Suggestions: (1) Physical education teachers are able to guide and direct students' talents. (2) Students are expected to join sports clubs.